Recent updates on treatment of ocular microbial infections by stem cell therapy: a review - Teh, Seoh Wei; Mok, Pooi Ling; Abd Rashid, Munirah; Bastion, Mae-Lynn Catherine; Ibrahim, Normala; Higuchi, Akon; Murugan, Kadarkarai; Mariappan, Rajan; Subbiah, Suresh Kumar (MDPI, 2018)
Ocular microbial infection has emerged as a major public health crisis during the past two decades. A variety of causative agents can cause ocular microbial infections; which are characterized by persistent and destructive inflammation of the ocular tissue; progressive visual disturbance; and may result in loss of visual function in patients if early and effective treatments are not received. The conventional therapeutic approaches to treat vision impairment and blindness resulting from microbial infections involve antimicrobial therapy to eliminate the offending pathogens or in severe cases; by surgical methods and retinal prosthesis replacing of the infected area. In cases where there is concurrent inflammation, once infection is controlled, anti-inflammatory agents are indicated to reduce ocular damage from inflammation which ensues. Despite advances in medical research; progress in the control of ocular microbial infections remains slow. The varying level of ocular tissue recovery in individuals and the incomplete visual functional restoration indicate the chief limitations of current strategies. The development of a more extensive therapy is needed to help in healing to regain vision in patients. Stem cells are multipotent stromal cells that can give rise to a vast variety of cell types following proper differentiation protocol. Stem cell therapy shows promise in reducing inflammation and repairing tissue damage on the eye caused by microbial infections by its ability to modulate immune response and promote tissue regeneration. This article reviews a selected list of common infectious agents affecting the eye; which include fungi; viruses; parasites and bacteria with the aim of discussing the current antimicrobial treatments and the associated therapeutic challenges. We also provide recent updates of the advances in stem cells studies on sepsis therapy as a suggestion of optimum treatment regime for ocular microbial infections.